Makna dan Fungsi Kearifan Budaya Lokal Tradisi Nyadran Bagi Masyarakat Sobowono - Ahmad Rickianto Afandi (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2023)
This research was conducted to determine the implementation of the nyadran tradition and the function of the nyadran tradition in the local cultural wisdom of the people of Sobowono Hamlet, Ketundan Village, Pakis District, Magelang Regency, Central Java Province. The nyadran tradition is the data in this study sourced from the head of Sobowono Hamlet and data collection using observation techniques, interview techniques, and documentation techniques. In analyzing the data is done in several stages. This stage is divided into the stage of searching for data, the stage of observation and documentation, the stage of determining informants, interviews, classifying data, and concluding data. The results of this study indicate that the nyadran tradition in Sobowono Hamlet, Ketundan Village, Pakis District, Magelang Regency, Central Java Province has a function as a cultural preservation so that future generations can know and understand this nyadran tradition. Apart from that, there is also a function as an expression of gratitude to Gusti Prince or God Almighty who has given blessings and enjoyment to the people of Sobowono Hamlet, and the last function is as social interaction, namely the people of Sobowono Hamlet take advantage of this nyadran tradition as a place to strengthen ties of friendship. and also the harmony of the people of Dusun Sobowono.